Invasive mole diagnosed as vascular malformation of uterus: a case report - Bhattacharjee, Surjyatapa; Nath, Pranoy; Choudhury, Shabir Ahmed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Gestational trophobalstic neoplasia encompasses invasive mole, placental site trophoblastic tumor, epitheloid trophoblastic tumor and choriocarcinoma. Here we report a 27 year old woman with invasive mole with severe anaemia who was initially misdiagnosed as a case of incomplete abortion with vascular malfomarmation of uterus. In view of uncontrolled bleeding per vaginum, nonspecific ultrasound findings and H/O failed dilatation and evacuation, exploratory laparotomy was decided upon and intraoperative finding was invasive mole. Hysterectomy was done.